The role of family-friendly practices and career aspirations on employees’ turnover intentions: organizational commitment as a mediator - Campos, Maria Isabel do Carmo (2022)
The literature on family-friendly practices is still scarce. These practices are designed to help employees manage their work-life balance and research has demonstrated that they have positive consequences for the organizations and countries that employ these practices. This dissertation aims at comprehending how family-friendly practices impact turnover intentions using organizational commitment as a mediator and career aspirations as a moderator. Our sample (N = 237) consisted on employees that work on the private sector in Portugal, and that have at least one child aged 12 yearsold or younger. We predict that family-friendly practices will diminish turnover intentions both directly, and indirectly through affective commitment, normative commitment, or continuance commitment. Further, we hypothesize that career aspirations will have a moderation effect on the relationship between family-friendly practices and each of the dimensions of organizational commitment, and a moderation effect in the relationship between family-friendly practices and turnover intentions. Our results show that family-friendly practices do indeed diminish turnover intentions through the mediating effect of affective commitment. Normative commitment and continuance commitment didn’t generate significant results. The same happened for career aspirations. This dissertation is, at last, completed with a discussion of our findings and recommendations for future research on the matter.